Errors in Writing - B. Budiyono (Magister Scientiae, 2012)
Errors in language learning may be analyzed by means of the combination of surface and linguistic strategies. The errors in this paper were collected from the end-of-term test of Writing II of group A. The data were classified as addition, omission, and substitution. No ordering errors were found. There are many, however, data of errors about Indonesian food names.